Spatio‐temporal video contrast enhancement. Issue 6 (1st August 2013) - Celik, Turgay
Abstract : A video contrast enhancement algorithm which automatically enhances the contrast of a video using spatial and temporal information is proposed. The algorithm is based on the observation that the contrast in a video frame can be improved by increasing the grey‐level differences between each pixel of the video frame and its neighbouring pixels. Furthermore, such an improvement should be smooth in between consecutive video frames so that continuum of contrast improvement is achieved. A two‐dimensional (2D) histogram of a video frame is constructed using mutual relationship between each pixel and its neighbouring pixels. For each video frame, a 2D target histogram is computed by considering 2D histogram of the video frame, 2D uniformly distributed histogram, and the 2D histograms of forward and backward neighbouring video frames. The contrast enhancement of the video frame is achieved by mapping the diagonal elements of the 2D input histogram to the diagonal elements of the 2D target histogram. The proposed algorithm is easy to implement and is thus suitable for real‐time contrast enhancement applications.